EU and IFAD Review of CGIAR Research Programme 7: Climate Change, Agriculture and Food Security (CCAFS) - Jobbins, G; Pillot, D (2013)
This review was commissioned to evaluate European Commission (EC) contributions to the CGIAR Research Programme (CRP) on Climate Change, Agriculture and Food Security (CCAFS) in 2011. The review is framed around evaluation of processes and tools in the context of the current CGIAR reform process rather than observed impact of a specific project. Also attached is the official response of the CCAFS Program Management Committee to the review.